Analysis of the Influence of External Factors of Sharia Bank on Non-Performing Financing (NPF) of Indonesian Sharia Commercial Banks - Khairiyah, Imamah; Lubis, Fauzi Arif; Nasution, M. Lathief Ilhamy (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
Islamic banking in Indonesia has grown rapidly in recent years. However, along with its development, Islamic banking also faces various risks, one of which is credit risk which can result in Non-Performing Financing (NPF) or non-performing loans. NPF is an important indicator that can affect banking stability. Therefore, it is important to control the factors that can affect the level of NPF in Islamic banks. This study aims to examine the effect of inflation, BI Rate, and exchange rates on Non-Performing Financing (NPF) in Islamic banking in Indonesia. NPF is an important indicator that can affect banking stability and inflation control, the BI Rate, and the exchange rate is the factors that can affect the level of NPF in Islamic banks. This study uses a method with a quantitative approach and with a sample of 264 and removes outliers to 141 observational samples using multiple linear regression analysis techniques. The partial and simultaneous results of the research on inflation, the BI Rate, and the exchange rate on Non-Performing Financing (NPF) have a significant influence. The importance of controlling inflation, the BI Rate, and the exchange rate in managing credit risk and preventing NPFs. Inflation has an inverse effect on NPF, meaning that when inflation rises, NPF tends to fall. The BI Rate has a significant impact on a bank’s ability to manage credit and credit risk, the higher the BI Rate, the greater the possibility of an NPF. Furthermore, changes in the exchange rate can affect the credit risk that must be borne by banks in managing credit, the lower the exchange rate, the greater the possibility of an NPF.